Potentiometric sensing platform for selective determination of Pregabalin in pharmaceutical formulations - Eman H El-Naby (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
Pregabalin is a structural analogue of, but functionally unrelated to, the naturally occurring neurotransmitter -aminobutyric acid (GABA) with potent analgesic, anticonvulsant and anxiolytic activity. The abuse potential of pregabalin is a well-documented with high risk of addiction that may be fatal with overdoses particularly, among opiate addicts and polydrug use dependency syndrome, consequently, it is very pertinent to determine pregabalin in a sensitive and selective manner. Herein, for the fi rst time the use of β-cyclodextrin:phosphomolybdic acid organic-inorganic hybrid material as a neutral ionophore in polymeric membrane based selective sensors for the determination of pregabalin in its pharmaceutical formulations has been reported.